Leaf area and intermittent misting on hop plants propagation by stem cuttings - Gomes, Erik Nunes; Machado, Marília Pereira; Miola, José; Deschamps, Cícero (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
Hop (Humulus lupulus L.) is a plant with economic importance due to its use in the brewing industry. The cones produced by the species contain the main substances responsible for the beer’s bitterness and aroma. Hop plants cultivation in Brazil is still incipient and information on efficient methods for its propagation in this context are scarce. The objective of the present study was to evaluate the effect of different leaf areas (two whole leaves, two leaves in half, one whole leaf, one leaf in half and without leaves) in herbaceous stem cuttings planted in environments with and without intermittent misting. The experiment was conducted in a greenhouse in Curitiba-PR, Brazil (25º25’40 “S and 49º16’23” W). After 30 days of planting, the survival, rooting, sprouting and leaf retention percentages, roots number, average roots length and roots and sprouts dry mass were evaluated. Cuttings with one or two whole leaves and two leaves in half in the misting environment showed the highest rooting percentages (between 90.0 and 97.5%). In the without misting environment, the highest values were observed in cuttings with one or two leaves in half and one whole leaf (between 62.5 and 72.5%). Leafless cuttings had low survival percentages (2.5% in both environments). Under intermittent misting conditions it is recommended to prepare stem cuttings with one or two whole leaves and, in the absence of control over the environment humidity, cuttings with one whole leaf are recommended.